Ethical Issues at the Beginning of Life - In Gyu Song (Korean Society of Neonatology, 2021)
With improvements in the survival rate of high-risk newborns, the need for ethical considerations is increasing. In the event of a conflict of opinion between the parents and the medical staff about the treatment decision, often there are concerns about who needs to make the decision that would be in the best interest of the baby. In this article, focusing on the guidelines for neonatal resuscitation revised in 2020, ethical issues that may arise before and soon after birth are reviewed. In addition, the considerations in determining the treatment direction for neonates with poor prognosis and the care required for babies and their families during the neonatal period have been investigated. Decisions about withholding or discontinuing neonatal resuscitation are often time-pressed since they are often made when labor is imminent or are needed shortly after the baby's birth. The recommendations put forth by the American Heart Association in 2020 may be referred toward decision making. Since the medical condition of high-risk newborns also often change rapidly following admission, it becomes necessary to review the treatment goals periodically. Though principles suggested by the American Academy of Pediatrics regarding the treatment decision of high-risk newborns are available, in Korea, it is also essential to consider the country's law while discussing life-sustaining treatment. Improving the patient's quality of life is equally important as deciding treatment plans and approaches for sustaining life. Toward this, it becomes necessary that the medical staff treating high-risk newborns be educated on palliative care and build a support system.